New neolignans and a phenylpropanoid glycoside from twigs of miliusa mollis - Sawasdee,K. (Multidisciplinary Digital Publishing Institute (MDPI), 2015)
From the twigs of Miliusa mollis Pierre, three new compounds including (2S,3S)-2,3-dihydro-2-(4-methoxyphenyl)-3-methyl-5-[1(E)-propenyl]benzofuran, (7S,8S)- threo-→δ8'-4-methoxyneolignan and tyrosol-1-O-β-xylopyranosyl-(1→6)-O-β-glucopyranoside were isolated, along with seven known compounds. Their structures were elucidated through analysis of their spectroscopic data. © 2010 by the authors.